Simulation of Unreinforced Masonry Beams Retrofitted with Engineered Cementitious Composites in Flexure - Hendriks, Max A N; Billington, Sarah L.; Kyriakides, Marios (My University, 2012)
A two-dimensional non-linear finite-element analysis micro-modeling approach to simulate unreinforced masonry beams in bending is extended to include a retrofit with a thin layer of ductile fiber-reinforced cement-based material referred to as engineered cementitious composite (ECC). The retrofit method is one that has been demonstrated to add significant ductility to unreinforced masonry infill walls under in-plane cyclic loading and is further expected to enhance out-of-plane bending resistance. The objective of the research is to identify and propose a modeling approach for this complex system of four materials and three different types of interface using basic material properties and established model parameters for future analyses of the retrofit system in structural applications. Of the two geometric models investigated, a simplified approach using expanded brick units with zero-thickness mortar elements is recommended and validated. Brick-mortar interface opening, cracking of the ECC layer below the mortar joints, and failure of the ECC were captured well. The simulated response is found to be particularly sensitive to the adopted constitutive model of the ECC. Research areas for enhancing the ability of the adopted modeling approaches in predicting the response of this complex system, are identified.
Keywords: Computer simulation; Finite element method; Masonry